2014
DOI: 10.1186/1741-7007-12-23
|View full text |Cite
|
Sign up to set email alerts
|

Colonizing while migrating: how do individual enteric neural crest cells behave?

Abstract: BackgroundDirected cell migration is essential for normal development. In most of the migratory cell populations that have been analyzed in detail to date, all of the cells migrate as a collective from one location to another. However, there are also migratory cell populations that must populate the areas through which they migrate, and thus some cells get left behind while others advance. Very little is known about how individual cells behave to achieve concomitant directional migration and population of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 79 publications
6
55
0
Order By: Relevance
“…Consistent with this latter hypothesis, MMP2 inhibition slows ENCDC migration (66). Preferential ENCDC migration along neurites (48,67) might also help cells navigate gut mesenchyme to preexisting gaps in the ECM. These hypotheses might explain why chain migration is more efficient than migration by isolated ENCDCs.…”
Section: Chain Migration and Cell Adhesionsupporting
confidence: 63%
See 2 more Smart Citations
“…Consistent with this latter hypothesis, MMP2 inhibition slows ENCDC migration (66). Preferential ENCDC migration along neurites (48,67) might also help cells navigate gut mesenchyme to preexisting gaps in the ECM. These hypotheses might explain why chain migration is more efficient than migration by isolated ENCDCs.…”
Section: Chain Migration and Cell Adhesionsupporting
confidence: 63%
“…One hypothesis is that cells at the front of the migrating ENCDC chain pull trailing ENCDCs via L1CAM-mediated adhesion. This seems unlikely, as migrating ENCDCs constantly change position, moving over each other (47,48). Another possibility is that ENCDCs enhance bowel colonization by altering ECM to enhance migration (65) or by degrading ECM to create spaces through which to migrate.…”
Section: Chain Migration and Cell Adhesionmentioning
confidence: 99%
See 1 more Smart Citation
“…NC cells emerge from the dorsal neural tube and are sculpted by intrinsic and extrinsic signals into discrete, multicellular streams throughout the head and trunk (Kulesa and Gammill, 2010). Analysis of cell behaviors from in vivo time-lapse imaging in chick Fraser, 1998, 2000;Teddy and Kulesa, 2004;Kulesa et al, 2008;McKinney and Kulesa, 2011;Ridenour et al, 2014) and in chick and mouse intestine (Young et al, 2004(Young et al, , 2014Nishiyama et al, 2012) has shown that there are regional differences in cell speed, direction, proliferation, calcium activity and cell morphology depending on cell position within an NC migratory stream. We previously showed that a computational model of NC cell migration, using the chick cranial NC cell behavioral data, predicted that successful cell persistence of direction and stream cohesion would result from the presence of unique lead and trailing subpopulations (McLennan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike enteric neurons, which are located exclusively within enteric ganglia, enteric glial cells (EGCs) are also found within interganglionic tracts, the smooth muscle layers, and the lamina propria of the mucosa (7)(8)(9). Both lineages of the ENS are derived from neuroectodermal progenitors, which delaminate from the neural crest and colonize the gut during embryogenesis (10)(11)(12)(13)(14). Enteric neurogenesis commences as soon as neural crest cells invade the gut (in the mouse at around embryonic day 9.0-9.5), peaks at mid-gestation, and continues, albeit at a decreasing pace, for the remaining fetal period and early postnatal life, until it terminates after weaning (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%